CFD modelling of slag fuming, with focus on freeze-lining formation - C M. G Rodrigues; M Wu; M Chintinne; A Ishmurzin; G Hackl; N Voller; A Ludwig; A Kharicha (The Australasian Institute of Mining and Metallurgy, 2024)
Slag fuming (SF) is a critical process for recycling zinc-containing slags, but the corrosive nature of molten slag poses challenges to the reactor durability. The freeze-lining (FL) technique offers a solution by forming a protective layer on the reactor wall. It requires intensive cooling using watercooled jackets, which can stabilise the FL while compromising the energy efficiency of the process. This study presents a computational fluid dynamic (CFD)-based model to optimise the SF process by considering FL formation and its impact on heat transfer and reactor wall temperature. A volumeof- fluid (VOF) model is coupled with a mixture continuum (MC) solidification model to capture the intricate multiphase flow dynamics within the SF furnace. Two FL types are considered: FL solidifying on the reactor wall in the slag bath region; and FL solidifying on the reactor wall in the freeboard region. The FL of the first type forms when the slag temperature drops below liquidus temperature. The FL of the second type only forms when a splash-induced slag droplet collides with the freeboard wall and solidifies. A series of splashing events are necessary to coat the freeboard wall. The simulation was run until a global energy balance was reached. This means that the heat losses from the water-cooled jacket, bottom wall, outlet and fuming balance the heat gains from the hot gas injected through the submerged plasma torches. The increase in FL thickness, due to its low thermal conductivity, reduces the heat losses through the reactor walls. The calculated FL thickness and heat fluxes were in good agreement with industrial data, validating the model’s credibility. The simulation results provided valuable insights into the fuming process, including slag bath temperature evolution, slag splashing dynamics, FL formation patterns, local heat fluxes through the reactor wall and overall energy balance. These findings can inform process optimisation strategies to enhance the energy efficiency and sustainability of SF operations. The authors have built a prior version of the model framework and applied it to simulate FL formation in an electric smelting furnace (ESF). The results from both the ESF and the current SF highlight the applicability of such model framework to a range of industrial processes involving FL formation. This model framework can ultimately contribute to more energy-efficient and sustainable industrial operations.